Investigation of genetic polymorphism at β-casein A1/A2 loci and association analysis with production & reproduction traits in Vrindavani crossbred cows. Issue 7 (12th December 2022) - Kumar, Adesh; Kumar, Sushil; Singh, Ran Vir; Chauhan, Anuj; Kumar, Amit; Sonwane, Arvind; K, Ilayakumar; Singh, Rahul
Abstract: Casein constitutes approximately 80% of the total protein in bovine milk and is regarded as a high-quality dietary protein embracing all the nine essential amino acids. However, the contested physiological effect of a bioactive peptide released upon digestion of a β-casein milk protein variant originating from a cow of a particular genetic makeup has evoked wide interest in research and industry. Present investigations were carried out to genotype the polymorphism in milk β-casein gene, delineate the seasonal, periodic, and parity variations in production and reproduction traits, and examine the genetic association between β-casein genotypes and production, and reproduction traits in Vrindavani crossbred cows. The study revealed that all three types of genotypes viz. A1A1, A2A2 and A1A2 were present in the Vrindavani crossbred population with genotypic frequencies of 12.3%, 39.6% and 48.1% respectively. The least-squares analysis revealed that the season of calving, period of calving, and parity affected several production and reproduction traits of Vrindavani cows significantly. It was found that β–Casein A1/A2 genotype had a significant effect on economic traits viz. LL ( p   ≤  0.05), MY/LL ( p   ≤  0.05), and Fat% ( p   ≤  0.05) in Vrindavani crossbreds. The findings uncover the genetic constitution of the crossbreds for β-casein locus and emphasize its relationship with important economic traits that can aid in devising selection goals.